Web application for patients - Leong, Pui Cheng (2015)
With the rising healthcare standard in the current digitalized society, a clinic patient or hospital patient seeks for fast and efficient ways to access medical information. One of the technologies that provides the fastest access to information is through the web, and hence gives rise to a need of a Patient Information System. It centralizes all the patient medical information and provide a common platform for medical personnel and patient to access the same information. It is currently insufficient for a patient to own an account and just view his or her past billing information. With an existing Patient Information System as a baseline, more patient-friendly services are required to add into the system. The tools and technologies used to enhance the system includes ASP.NET Framework C# and Microsoft SQL. The approach is to integrate the new features with the existing features (e.g. login, account management, billing reports). The new patient-friendly services includes allowing a patient to view his or her medical records, manage his or her consultations and appointments, and locate any nearby clinics. With these new services added, a patient of a clinic or hospital reduces the need to visit each and every visited clinic or hospital for medical records, reduces the manual administrative booking process, or finding the exact location of a clinic and hospital. These features reduce unnecessary travel journey and provide an ease of convenience for patients to access his or her medical information. These improvements provides faster and better healthcare support from medical personnel to patient.